Comparison of high dynamic range images (HDRI) rendering technique with normal rendering for integrating 3D architectural model into 2D local environment - Aishah , A. R.; Mohd Izani , Z. A.; Rafi, A. (2006)
This paper presents our attempt to explore and utilize High Dynamic Range Images (HDRI) as a method to generate photorealistic renderings, particularly in local 3D architectural visualizations. First we present an overview of HDRI, the definition, application and advantage. For the purpose of experiment, a database of HDR images have been collected and generated. This consists of indoor and outdoor images, and these images have been converted to HDRI using special software known as HDRIshop. An experiment has been carried out to compare the results of HDRI rendering and normal (traditional) rendering in terms of quality, rendering time and memory usage. Based on the results, it has shown that HDRI rendering has major advantage over normal rendering such as it produce more realistic rendering with less rendering time and memory usage. Finally the authors conclude the rendering quality and the effectiveness of the methods discussed and suggests some recommendation to further explore and expose the method in the field of architectural visualizations.